Clinical Study of Single-Stranded Oligonucleotide RO7062931 in Healthy Volunteers and Patients With Chronic Hepatitis B - Edward Gane (2022)
Background and Aims: RO7062931 is an N-acetylgalactosamine (GalNAc)-conjugated single-stranded locked nucleic acid oligonucleotide complementary to HBV RNA. GalNAc conjugation targets the liver through the asialoglycoprotein receptor (ASGPR). This two-part phase 1 study evaluated the safety, pharmacokinetics, and pharmacodynamics of RO7062931 in healthy volunteers and patients with chronic hepatitis B (CHB) who were virologically suppressed. Approach and Results: Part 1 was a single ascending dose study in healthy volunteers randomized to receive a single RO7062931 dose (0.1-4.0 mg/kg), or placebo. Part 2 was a multiple ascending dose study in patients with CHB randomized to receive RO7062931 at 0.5, 1.5, or 3.0 mg/kg or placebo every month for a total of 2 doses (Part 2a) or RO7062931 at 3.0 mg/kg every 2 weeks, 3.0 mg/kg every week (QW), or 4.0 mg/kg QW or placebo for a total of 3-5 doses (Part 2b). Sixty healthy volunteers and 59 patients received RO7062931 or placebo. The majority of adverse events (AEs) reported were mild in intensity. Common AEs included self-limiting injection site reactions and influenza-like illness. Supradose-proportional increases in RO7062931 plasma exposure and urinary excretion occurred at doses ≥3.0 mg/kg. In patients with CHB, RO7062931 resulted in dose-dependent and time-dependent reduction in HBsAg versus placebo. The greatest HBsAg declines from baseline were achieved with the 3.0 mg/kg QW dose regimen (mean nadir ~0.5 log10 IU/mL) independent of HBeAg status. Conclusions: RO7062931 is safe and well tolerated at doses up to 4.0 mg/kg QW. Supradose-proportional exposure at doses of 3.0-4.0 mg/kg was indicative of partial saturation of the ASGPR-mediated liver uptake system. Dose-dependent declines in HBsAg demonstrated target engagement with RO7062931.